Clinical implementation of minimally invasive esophagectomy - Heinz Wykypiel; Philipp Gehwolf; Katrin Kienzl-Wagner; Valeria Wagner; Andreas Puecher; Thomas Schmid; Fergül Cakar-Beck; Aline Schäfer (BMC Surgery)
Summary Background Minimally invasive surgery is becoming the method of choice for the resection of esophageal cancer worldwide. Methods: Retrospective analysis of prospectively collected clinical data in a tertiary care center with a detailed description of the course of the program. Results A total of 136 transthoracic esophageal resections were performed between 2010 and 2023. The study group included 116 operations, 69 of which were fully minimally invasive and 47 hybrid. 80.0% of the study group underwent surgery using a multimodality approach. The median operation time was 431 min (± 103). The R0 resection rate was 100%. Forty-two patients (36.2%) had no postoperative complications. The postoperative Clavien-Dindo > IIIb morbidity was 27%. The postoperative 90-d mortality rate was 1.7%. The average number of lymph nodes removed in the last quarter of cancer patients was 31. The anastomotic insufficiency rate for reoperation was 4% (Ivor-Lewis 4.2%, McKeown 5%). Conclusions With extensive expertise in high-end minimally invasive abdominal and thoracic surgery, implementation of a minimally invasive esophageal resection program with a clinical and oncologic outcome within generally accepted limits is feasible.